Discrete-phase-randomized coherent state source and its application in quantum key distribution. (13th May 2015) - Cao, Zhu; Zhang, Zhen; Lo, Hoi-Kwong; Ma, Xiongfeng
Abstract: Coherent state photon sources are widely used in quantum information processing. In many applications, such as quantum key distribution (QKD), a coherent state functions as a mixture of Fock states by assuming that its phase is continuously randomized. In practice, such a crucial assumption is often not satisfied, and therefore the security of existing QKD experiments is not guaranteed. To bridge this gap, we provide a rigorous security proof of QKD with discrete-phase-randomized coherent state sources. Our results show that the performance of the discrete-phase randomization case is close to its continuous counterpart with only a small number (say, 10) of discrete phases. Compared to the conventional continuous phase randomization case, where an infinite amount of random bits are required, our result shows that only a small amount (say, 4 bits) of randomness is needed.